Opportunities for Expanding Access to Veterinary Care: Lessons From COVID-19 - Smith, Sage M.; George, Zachary; Duncan, Colleen G.; Frey, Danielle M. (Frontiers in Veterinary Science, 2022)
The COVID-19 pandemic impacted people and professions around the world, including veterinary medicine. The epidemiology of SARS-CoV-2 broadened the definition of vulnerability in human populations, and the virus’ economic impacts exacerbated well-established financial barriers to providing equal access to medical care. The objective of this study was to explore how the pandemic was impacting access to companion animal care in the months March-September of 2020, with a focus on traditionally vulnerable as well as newly vulnerable populations. Additionally, this study sought to identify areas on which the veterinary profession can focus in order to help increase access to veterinary care, including the veterinary school curriculum, continuing education, and telemedicine. We conducted surveys and interviews with animal owners (n=1009), veterinarians and clinic staff (n=516), and access to veterinary care organizations (n=17). Collectively, these responses highlighted how the COVID-19 pandemic created new, and amplified existing, issues with accessing and providing veterinary care. Three critical themes arose; 1) opportunities for further learning for the veterinary profession; including curricula around telemedicine, financially resilient business models and understanding health disparities and vulnerable populations; 2) a need for a network of collaboration and communication across veterinary clinics and access to care organizations and 3) future preparedness for health, economic or other crises response. Overall, the pandemic emphasized the complexity of access to care, as well as the role of veterinarians in public health. This information can be used to develop strategies to aid in increased access to veterinary care now and in the face of future disasters.